Frames of reference for pediatric occupational therapy - Paula Kramer; Jim Hinojosa; Tsu-Hsin Howe (Philadelphia, Pennsylvania : Wolters Kluwer, 2019)
"The new edition of Kramer, Hinojosa, Howe/Frames of Reference for Pediatric Occupational Therapy will continue to provide that frame of reference blueprints for future and current Occupational Therapists who treat children. A frame of reference is an "accepted structure for organizing theoretical material and translating that into practice." The model provides a blueprint for taking the abstract concepts of OT theory (or theories) and elevating those ideas to actions that can be used in practice. This fourth edition continues to focus on the importance of occupation, and all of the frames of reference have been revised to include examples that relate to the importance of occupation and active involvement in a meaningful life. This edition includes three new frames of references, including the STAR frame of reference for working with children with sensory processing disorders, a frame of reference for working with children with anxiety and depression, and a strength-based frame of reference for working with adolescents with autism. A major thrust of this revision was the updating of material in all chapters. Content was overhauled to reflect changes in theory and practice. In addition, all frames of reference have a new section called Supporting Evidence that reflects the importance of research to practice. For this edition, we continued to use the language of the World Health Organization's International Classification of Functioning, Disability, and Health (ICF). Incorporation of ICF language broadens the appeal of the book. This language resulted in an emphasis on the importance of the child's ability to participate in meaningful activities of life (occupations)"
Keywords: Adolescent; Child Development